2018
DOI: 10.1515/ms-2017-0089
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear ∗-Jordan triple derivations on von Neumann algebras

Abstract: LetB(H) be the algebra of all bounded linear operators on a complex Hilbert spaceHand 𝓐 ⊆B(H) be a von Neumann algebra with no central summands of typeI1. ForA,B∈ 𝓐, define byA∙B=AB+BA∗a new product ofAandB. In this article, it is proved that a map Φ: 𝓐 →B(H) satisfies Φ(A∙B∙C) = Φ(A) ∙B∙C+A∙ Φ(B) ∙C+A∙B∙Φ(C) for allA,B,C∈ 𝓐 if and only if Φ is an additive *-derivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Therefore, studying Lie triple derivations enables us to treat both important class of Jordan derivations and Lie derivations simultaneously. More recently, Jordan-type derivations on triangular algebras, prime rings, matrix algebras, nest algebras and von Neumann algebras are considered by Lin, Qi and Zhao et al, see [33,53,56]. An R-bilinear mapping ϕ : A × A −→ A is a Jordan biderivation if it is a Jordan derivation with respect to both components, implying that ϕ(x • y, z) = ϕ(x, z) • y + x • ϕ(y, z) and ϕ(x, y • z) = ϕ(x, y) • z + y • ϕ(x, z) for all x, y ∈ A.…”
Section: Related Topics For Further Researchmentioning
confidence: 99%
“…Therefore, studying Lie triple derivations enables us to treat both important class of Jordan derivations and Lie derivations simultaneously. More recently, Jordan-type derivations on triangular algebras, prime rings, matrix algebras, nest algebras and von Neumann algebras are considered by Lin, Qi and Zhao et al, see [33,53,56]. An R-bilinear mapping ϕ : A × A −→ A is a Jordan biderivation if it is a Jordan derivation with respect to both components, implying that ϕ(x • y, z) = ϕ(x, z) • y + x • ϕ(y, z) and ϕ(x, y • z) = ϕ(x, y) • z + y • ϕ(x, z) for all x, y ∈ A.…”
Section: Related Topics For Further Researchmentioning
confidence: 99%
“…Note that, unlike von Neumann algebras which are always weakly closed, a standard operator algebra is not necessarily closed. The current work together with [7,[10][11][12][13][23][24][25][26] indicates that it is feasible to investigate * -Jordan-type derivations and * -Lie-type derivations on operator algebras under a unified framework-η- * -Jordan-type derivations. We have good reasons to believe that characterizing η- * -Jordan-type derivations on operator algebras is also of great interest.…”
Section: Related Topics For Future Researchmentioning
confidence: 99%
“…* -Jordan-type derivations on operator algebras have been studied by several authors. Let H be a complex Hilbert space and B(H) be the algebra of all bounded linear operators on H. Li et al in [10] showed that if [26]. Taghavi et al [23] and Zhang [25] independently investigate * -Jordan derivations on factor von Neumann algebras, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similar conclusion have been obtained in [11] by Bell and Kappe. Zhao and Li, in [12], proved that every nonlinear * -Jordan triple derivation on von Neumann algebras is an additive * -derivation. For other similar results about Jordan triple derivations (nonlinear Jordan triple derivable mappings), we refer the readers to [13][14][15] and references therein, for more details.…”
Section: Introductionmentioning
confidence: 99%